การพัฒนารายวิชา ง 33102 งานอาชีพสู่อาเซียน สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 6 โรงเรียนโสภณศิริราษฎร์ จังหวัดราชบุรี - วรรณวิไลย วิไลรัตน์ (RMUTP Research Journal Sciences and Technology, 2014)
บทคัดย่อ การวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อพัฒนา ศึกษาประสิทธิภาพ และดัชนีประสิทธิผลของหลักสูตรรายวิชา ง 33102 งานอาชีพสู่อาเซียน รวมทั้งศึกษาความพึงพอใจและทักษะกระบวนการทำงานของผู้เรียนที่ศึกษารายวิชา ง 33102 งานอาชีพสู่อาเซียน กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ เป็นนักเรียนชั้นมัธยมศึกษาปีที่ 6 ภาคเรียนที่ 2 ปีการศึกษา 2555 โรงเรียนโสภณศิริราษฎร์ สำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 ราชบุรี จำนวน 65 คน จากการเลือกแบบเจาะจง (Purposive Sampling) เนื่องจากนักเรียนชั้นมัธยมศึกษาปีที่ 6 มีจำนวน 2 ห้องเรียน จึงเลือกศึกษาจากนักเรียนทั้งหมด เครื่องมือที่ใช้ในการวิจัยประกอบด้วย หลักสูตร แผนการจัดการเรียนรู้ แบบทดสอบ แบบสอบถามความพึงพอใจ และแบบประเมินทักษะกระบวนการทำงาน การวิเคราะห์ข้อมูลโดยใช้ค่าร้อยละ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า หลักสูตรและแผนการจัดการเรียนรู้รายวิชา งานอาชีพสู่อาเซียน สำหรับนักเรียน ชั้นมัธยมศึกษาปีที่ 6 มีประสิทธิภาพสูงกว่าเกณฑ์ 80/80 (85.75/87.30) มีค่าดัชนีประสิทธิผลสูงกว่าเกณฑ์ 0.50 (0.80) ผู้เรียนมีความพึงพอใจอยู่ในระดับมากที่สุด และผู้เรียนมีทักษะกระบวนการทำงานอยู่ในระดับมาก มีความเหมาะสม สามารถนำไปใช้ในการจัดการเรียนการสอน เพื่อเตรียมความพร้อมเข้าสู่ประชาคมเศรษฐกิจอาเซียน (AEC) ในโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาทุกแห่งได้ Abstract This research aimed to develop and study efficiency and effectiveness index of Vocational Course to ASEAN, as well as to study level of satisfaction and work process skills of students who study V 33102 Vocational Course to ASEAN. The samples in this research were 65 Twelfth Grade students who enrolled in second semester of academic year 2012 at Soponsirirat School, under the Secondary Education Service Area office 8, Ratchaburi province. The samples were selected by Purposive Sampling from two classes of Twelfth Grade students. Research tools consisted of curriculum, lesson plans, achievement test, students’ satisfaction survey questionnaire, and evaluation form of students’ work process skills. Data were statistically analyzed for Percentage, Means and Standard Deviation. Results revealed that Curriculum and lesson plans of Vocational Course to ASEAN for Twelfth Grade students had higher efficiency than the standard of 80/80 (85.75/87.30). Effectiveness index was also higher than the standard of 0.50 (0.80). Students’ satisfaction in instruction was in the highest level and students’ working skills were also at very good level. This means that the course is suitable and could be adopted to prepare students for ASEAN Economic Community in every school under the Secondary Educational Service Area Office.